The Evaluation of Promoting Ideas and Improving Life Through Movement’s Workshop Project - Ing-on Mai-on; Atcharaphan Changkeaw; Salakjit Kanalit; Paiboon Napranbun; Torsak Kaewjaratwilai (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
The research aims to study the result and approaches of applying knowledge from the promoting ideas and improving life through movement’s workshop project. The participants were 38 people. Research instruments were a questionnaire and a semi- structured interview. The research statistics were frequency, percentage, mean, standard deviation, and content analysis. The data was conducted after 2 weeks of training via online and telephone interviews. The results showed that 1) the participants able to apply the knowledge to integrate in teaching and learning, and apply them in practice, overall, is in the highest level. And is in the highest level in every aspects. 2) Approaches for applying knowledge to work is to apply the principles and knowledge gained to meet the objectives of the activities by designing activities according to the principles of movement correctly to continue to integrate in teaching and learning management.